2022
DOI: 10.3390/jcm11206051
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Considerations and Practice Recommendations Regarding the Use of Sodium-Glucose Cotransporter-2 Inhibitors

Abstract: Sodium-glucose cotransporter-2 inhibitors (SGLT-2is) (canagliflozin, dapagliflozin, empagliflozin, and ertugliflozin), although initially developed as glucose-lowering drugs, provide significant beneficial effects on cardiorenal outcomes, including heart failure, regardless of type 2 diabetes status. Integration of SGLT-2is into clinical practice requires practical guidance for physicians about their use. To overcome physicians’ clinical inertia for SGLT-2i use, including addressing safety, potentially a barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Diamonds show predictions for a random effects model adjusting for drug, outcome, and age subgroup, and whiskers and boxes show the observed hazard ratios and 95% confidence intervals in the source trial data. The data in this table were adapted from Figure 3 from [128] under the Creative Commons Attribution (CC BY) license.…”
Section: Sodium Glucose Co-transporter 2 Inhibitorsmentioning
confidence: 99%
“…Diamonds show predictions for a random effects model adjusting for drug, outcome, and age subgroup, and whiskers and boxes show the observed hazard ratios and 95% confidence intervals in the source trial data. The data in this table were adapted from Figure 3 from [128] under the Creative Commons Attribution (CC BY) license.…”
Section: Sodium Glucose Co-transporter 2 Inhibitorsmentioning
confidence: 99%
“…SGLT2is are in general safe drugs, but reported side effects such as diabetic ketoacidosis, and lower limb amputations appear to be barriers in prescribing them. A meta-analysis [119] has quantified risks and benefits of SGLT2i in patients with and without DM: the Number Needed to Treat to prevent one death (120) or one kidney disease progression event (48) dominated the Number Needed to Harm for the development of one lower limb amputation (309) or diabetic ketoacidosis event (636). For most patients, SGLT2i would accrue a 3-10 fold larger benefit than risk depending on the specific pair of outcomes considered [119].…”
Section: Sodium Glucose Co-transporter Two Inhibitorsmentioning
confidence: 99%
“…Diamonds show predictions for a random effects model adjusting for drug, outcome and age subgroup, whiskers-boxes show the observed hazard ratios and 95% confidence intervals in the source trial data. The data in this table was adapted from Figure 3 from [120] under the Creative Commons Attribution (CC BY) license.…”
Section: Sodium Glucose Co-transporter Two Inhibitorsmentioning
confidence: 99%
“…SGLT2 inhibitors have been initially used as a novel class of glucose-lowering agents by acting on SGLT2 in the renal tubules and inhibiting the reabsorption of filtered glucose in the kidneys. While safety concerns have been raised, including volume depletion, diabetic ketoacidosis, genitourinary infections, and hyperkalemia [22], large-scale clinical trials have not shown a substantial increase in adverse reactions compared to placebo groups [23,24]. In addition to glucose-lowering effects independent of insulin secretion, the advantages of SGLT2 inhibitors for diabetes management include weight loss without major hypoglycemic events, cardiovascular benefits supported by clinical trials, and prevention of nephropathy and renal function decline among patients with or without diabetes [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%